Detection of Norovirus in stool samples by RT-PCR from under five years age children hospitalized for acute gastroenteritis in Basrah, Iraq - Hazim Thwiny (مجلة علوم ذي قار, 2019)
Abstract 2 1 Department of Microbiology Hassan J. Hasony - College of Veterinary Medicine - College of Medicine - - University of Basrah University of Basrah Basrah/ Iraq E-mail: hazimt@yahoo.com